Radiolytic Reduction of Aqueous Solutions of a Commercial Reactive Dye in the Range 0-100KGY by CO60 Gamma Radiation Source - Taqmeem Hussain; Muhammad Shahbaz; Inam-ul-Haq; Hashim Farooq (Journal of Basic & Applied Sciences, 2021)
Gamma dosimetric behavior of the aqueous solutions of the Sandalfix Golden Yellow CRL (SGY-145) dye was studied. The sample solutions of two chemical natures i.e., Acidic and Alkaline; were irradiated by Co60 γ-sources in the range 0-100kGy. The “Control samples” were remained un-irradiated and also chemically neutral. The dosimetry was done in three phases i.e., Low, Intermediate and High, ranging from 100-1000Gy, 1-10kGy and 10-100kGy respectively. The found values of the “λmax” and the molar extinction coefficient “ε” of the dye were 467 nm and 3.4×103 mol-1cm-1respectively. The absorbance (A) of the aqueous solutions was studied at the absorption band maxima (λmax). The behavior of “Alkaline and Acidic solutions” was checked with the help of curve fitting